Análisis de Eficacia y Relación Costo Efectividad del Tratamiento de Rehabilitación Residencial por Adicción a Drogas con Consentimiento Sustituto en una Comunidad Terapéutica (2024)
To evaluate the investment costs and effectiveness of a drug addiction treatment is to know how to prioritize which type of intervention is the most effective in favoring addiction to a residential rehabilitation process with substitute consent. Drug addiction is a chronic disease and a public health problem that, added to the failure of therapeutic interventions, demonstrates a scientific error and a misuse of health system resources